Parental knowledge and satisfaction with newborn hearing screening in Saudi Arabia - Alothman, Noura I.; Alanazi, Ahmad A.; Alshenaifi, Sadeem S.; Alhadhban, Yara; Alateeq, Salma A.; Alhwaimel, Norah; Dolgum, Nouf (Frontiers in Pediatrics, 2024)
Objectives: Parental knowledge and satisfaction are critical for evaluating the newborn hearing screening (NHS) program. No studies have assessed both parental knowledge and satisfaction with the NHS program since its launch in Saudi Arabia. The study aimed to evaluate parents' knowledge and satisfaction with the NHS program in Saudi Arabia.Methods: This study included parents of children aged 3 years or younger who had undergone NHS. A questionnaire with 23 questions in Arabic assessed knowledge and satisfaction. Knowledge-related questions were developed by a focus group, while satisfaction-related questions were derived from the Parent Satisfaction Questionnaire with a Neonatal Hearing Screening Program.Results: A total of 796 parents participated. Overall, 92.8% reported that their newborns passed the screening, 1.6% reported that their newborns failed, and 5% were unaware of the NHS results. About 0.6% did not return for follow-up appointments due to unawareness of the need for follow-up. Only 29.6% received information about the NHS before the screening, and 44.7% reported receiving sufficient information about the results. Most parents (80.2%) were generally satisfied with the NHS program.Conclusions: Parents in this study were generally knowledgeable and satisfied with the NHS program. However, efforts are needed to improve the NHS program's effectiveness by increasing awareness and providing sufficient information on the necessity of NHS, test results, and follow-up appointments.